Sosialisasi kesehatan mental tentang perundungan kekerasan seksual dan perilaku intoleransi pada remaja - Elsi, Mariza; Setiarini, Sari; Gusti, Dalina (JOURNAL of Public Health Concerns, 2025)
Background: Violence in schools, including sexual violence, bullying, and intolerance, remains a serious problem that threatens the well-being of students. This is particularly concerning because it contrasts with the general perception that schools are safe environments free from crime because they are filled with educated individuals. Data from the Indonesian Child Protection Commission (KPAI) and the Federation of Indonesian Teachers' Unions (FSGI) in 2023 showed that the most common forms of violence experienced by students were physical violence (55.5%), verbal violence (29.3%), and psychological violence (15.2%). Purpose: To increase junior high school students' knowledge and awareness of the dangers of bullying, sexual violence, and intolerance in an effort to build positive character within the school environment. Method: This activity was held at SMP 16 Padang City in October 2025. The counseling session was attended by 67 seventh-grade students. The activity consisted of an interactive presentation using visual media that directly involved students. The questionnaire consisted of 15 questions, divided into two sections: 10 knowledge questions to measure students' understanding of the definition of violence, its types, and how to prevent and handle it. These questions were in multiple-choice and short-answer format. 5 behavioral questions aimed to measure changes in students' attitudes and behaviors after receiving the counseling, such as whether they felt more confident reporting violence they experienced or witnessed. These behavioral questions used a Likert scale (agree/disagree). Results: The average knowledge score before the counseling session was 59.6, with a range of 32-87. After receiving counseling on bullying, sexual violence, and intolerance, the average knowledge score increased to 86.0, with a range of 72-100. Conclusion: Through interactive outreach activities, participants more easily understand that bullying, sexual violence, and intolerance are behaviors that negatively impact mental health, for both victims and perpetrators. Students also become more able to assertively reject violence, respect differences, and report to authorities if actions threaten their own safety or the safety of others. Suggestion: It is hoped that sustainable programs related to violence prevention can be developed, involving an anti-violence task force team from all parties, including teachers, students, and school counselors. It is also hoped that regular activities in the form of anti-violence outreach or campaigns will be held, at least once a semester, so that the messages conveyed remain ingrained in students. Keywords: Bullying; Mental health; Prevention; School environment; Student behavior Pendahuluan: Kekerasan di lingkungan sekolah diantaranya kekerasan seksual, perundungan (bullying) dan intoleransi masih menjadi permasalahan serius yang mengancam kesejahteraan siswa di lingkungan sekolah. Hal ini di rasa miris karena kontras dengan pandangan umum bahwa sekolah merupakan lingkungan aman dari tindak kejahatan karena dipenuhi orang-orang terdidik. Data dari Komisi Perlindungan Anak Indonesia (KPAI) dan Federasi Serikat Guru Indonesia (FSGI) tahun 2023 menunjukkan bahwa bentuk kekerasan yang paling sering dialami siswa adalah kekerasan fisik (55.5%), verbal (29.3%), dan psikologis (15.2%). Tujuan: Untuk meningkatkan pengetahuan dan kesadaran siswa SMP mengenai bahaya perundungan, kekerasan seksual, dan intoleransi dalam upaya membangun karakter positif di lingkungan sekolah. Metode: Kegiatan ini dilaksanakan di SMP 16 Kota Padang pada bulan Oktober 2025. Jumlah peserta penyuluhan sebanyak 67 peserta terdiri dari siswa kelas VII. Kegiatan berupa presentasi interaktif menggunakan media visual yang melibatkan siswa secara langsung. Instrumen berupa kuesioner terdiri dari 15 pertanyaan, yang terbagi menjadi dua bagian, yaitu pertanyaan pengetahuan (10 pertanyaan) untuk mengukur pemahaman siswa mengenai pengertian kekerasan, jenis-jenis kekerasan, serta cara pencegahan dan penanganannya. Pertanyaan-pertanyaan ini berbentuk pilihan ganda dan isian singkat. Kemudian pertanyaan perilaku (5 pertanyaan), bertujuan untuk mengukur perubahan sikap dan perilaku siswa setelah mendapatkan penyuluhan, seperti apakah mereka merasa lebih percaya diri untuk melaporkan kekerasan yang mereka alami atau saksikan. Pertanyaan perilaku ini menggunakan skala Likert (setuju/tidak setuju). Hasil: Menunjukkan bahwa nilai rata-rata pengetahuan sebelum diberikan penyuluhan yaitu sebesar 59.6 dengan rentang nilai 32-87. Setelah diberikan penyuluhan perundungan kekerasan seksual dan Intoleransi nilai rata-rata pengetahuan responden meningkat menjadi sebesar 86.0 dengan rentang nilai 72-100. Simpulan: Melalui kegiatan penyuluhan yang interaktif, peserta lebih mudah memahami bahwa perundungan, kekerasan seksual, dan intoleransi merupakan perilaku yang berdampak negatif terhadap kesehatan mental, baik bagi korban maupun pelaku. Siswa juga menjadi lebih mampu untuk bersikap tegas menolak kekerasan, menghargai perbedaan, dan melapor kepada pihak berwenang apabila terjadi tindakan yang mengancam keselamatan diri atau orang lain. Saran: Diharapkan dapat mengembangkan program berkelanjutan terkait pencegahan kekerasan, dengan melibatkan tim satuan tugas anti-kekerasan dari semua pihak antara guru, siswa, dan konselor sekolah. Diharapkan juga, adanya kegiatan rutin berupa penyuluhan atau kampanye anti-kekerasan, minimal setiap semester, agar pesan yang disampaikan tetap tertanam dalam diri siswa.